The Implementation of the RC4 algorithm For Sale and Purchase Agreements Data Security On Notary Office - Trisna Setiawaty; Olven Manahan (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
Ksecurity wheel is one of the essential needs of the data, or information. With this regard the importance of the information or data by the party or person of interest. This research aims to design and build a system for data security deed of sale that can help the Notary / PPAT. The system was built using the RC4 (Rivest Code 4) which is a symmetric key cryptographic algorithms and is stream cipher, there is a process of encryption and decryption. The encryption is the process of encoding the original message or plaintext into ciphertext encrypted text. While decryption is the process of encoding back to cipherteksmenjadiplainteks (original data). This research resulted in a system that is able to change the data that can be read into the data that is not easily understood.